STRATEGIC IMPLEMENTATION AND FINANCIAL PERFORMANCE OF COMMERCIAL BANKS IN RWANDA:A CASE OF ACCESS BANK PLC - CYOMUHENDO, Linda G.; Safari, Ernest (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2022)
The reason of this investigate was to look at the part of key usage on money related execution of commercial banks in Rwanda and the taking after were particular targets: to decide the impact of checking technique on monetary execution of Get to Bank in Rwanda, to analyze the impact of communication technique on monetary execution of Get to Bank in Rwanda, and to evaluate the impact of competitive technique on budgetary execution of Get to Bank in Rwanda. The target populaces at Get to Bank Ltd comprised of 148 representatives who are in charge of actualizing diverse methodologies meaning from the organization to senior staffs in all divisions. The test estimate of 109 respondents was calculated by utilizing the equation of Taro Yamane. The survey was utilized as the most instruments for information collection and meet direct were utilized for head instructors. Since information collected were accumulated in computer through SPSS (Measurable Bundles for Social Sciences) Adaptation 20 and it was utilized for examination with factual specialized like rate, frequencies, and progressed measurable methods like relationship and chi-square which was utilized for testing the relationship between factors under study. Comes about to the primary objective a positive noteworthy relationship between directing clients and return on resources (r=.320**, p-value =0.001), return on value (r=0.0317, p-value =0.001). There were positive critical relationship between For Clear reason to be in trade and ROA (r=0.408*, p-value=0.048), clear reason to be in trade and NIM (r=0.716, p-value=0.000). The conclusion drawn from the third inquiries proved that competitive methodology was executed at the commercial banks and this has influenced its budgetary execution in Rwanda. All factors of different measurements ought to be put into the proper viewpoint, so as to assist the common workforce of the bank to get it the vital usage in put to realize the destinations of the bank. This will illuminate the representatives of the bank to scoff towards conveying administrations to improve the common procedure of the bank and to raise its execution.